Prevalence of Occupational Diseases among Small and Medium Industry Workers in Malaysia: A Systematic Review - Yusof, Muhammad Zubir; Nik Mahmod, Nik Ahmad Kamal; A. Rahman, Nor Azlina; Razali, Ailin; Samsuddin, Niza; Nik Mohamed, Nik Mohamed Nizan; Syed Jamaludin, Muhammad Shaqif; Mohd Roze, Amalina; Abdullah Hair, Ahmad Fitri (Faculty of Medicine, Universiti Teknologi MARA, 2019)
Occupational diseases are one of the major health problems related to workplace hazards. However, the epidemiological data for this problem is scarce especially among Small and Medium Industry (SMI) workers. These workers are vulnerable to occupational health problem due to lack of knowledge and implementation of health and safety in the workplace. In Malaysia, most of the SMI workers have limited coverage for basic occupational health services which may worsen their health. Thus, this article aims to provide a review on the burden of occupational health problems among them. The electronic and library searches were used to extract the information from both published and unpublished articles that were not limited to any year of publication until 2017. One hundred and ninety-six published articles and 198 unpublished articles were retrieved from the database. Only 19 published articles and 25 unpublished articles met the eligibility criteria. Prevalence data of occupational diseases/poisoning, including overall and body specific (musculoskeletal disorders) was extracted in raw data from the eligible studies. Prevalent statistics on occupational musculoskeletal diseases (1.3% - 97.6%), noise-induced hearing loss (29.4% - 73.3%), occupational skin diseases (10.5% - 84.3%), respiratory (1.9% - 92.2%) and occupational poisoning (14.9% - 17.7%) among the working population is different within published papers compared to unpublished ones. In Malaysia, there are no specific statistic that give a true picture of the burden of occupational diseases in the SMI. However, this review concludes that musculoskeletal diseases are significant occupational problems among SMI workers.